No Good Deed Goes Un-Litigated: The Pitfalls of the Title II Private Right of Action in a Market of Fiber Optic Innovation - Simard, Philippe (Science and Technology Law Review, 2018)
The reclassification of broadband as a Title II service was a giant economic success for edge providers. The FCC, by subjecting ISPs to “common carrier” regulation and outlawing practices like “throttling,” transferred the financial burden of network build-out onto ISPs by law.31 Similarly, the FCC entertained the possibility that edge providers would be forced by ISPs to help pay for infrastructure build-out when they repealed the reclassification. Whether or not one supports these changes depends on preferred policy positions, and scholars on both sides thoroughly commented on the debate.32 More importantly, for the purposes of this Note, the model of net neutrality regulation would give edge providers an important regulatory weapon built into Title II—the private right of action. This regulatory weapon could threaten the basic fairness of the Internet marketplace and should be avoided if net neutrality is to be made law again.